2019
DOI: 10.25304/rlt.v27.2124
|View full text |Cite
|
Sign up to set email alerts
|

Animating student engagement: The impacts of cartoon instructional videos on learning experience

Abstract: In the modern age of education, students increasingly demand engaging, customized multimedia content. Animation constitutes a powerful pedagogical tool by combining audio messages with tailored visual cues and graphics, to serve the dual functions of explaining complex concepts and engaging student interest in the learning process. This study explores the use of a series of animated videos to teach advanced accounting at an Australian university. Based on survey responses from 254 undergraduate students over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 72 publications
0
24
1
1
Order By: Relevance
“…This is seen in the study of Poggiali [28] to which the findings showed that learners exhibited enthusiasm when animation is also applied as a medium of instruction. Additionally, animated visual cues and customized media content as pedagogical tools can simulate student interest in the learning process [29], [30]. For example, one study in the Philippines showed that a developed mobile game intended for basic English language learning can improve student performance particularly in vocabulary, spelling, and grammar [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is seen in the study of Poggiali [28] to which the findings showed that learners exhibited enthusiasm when animation is also applied as a medium of instruction. Additionally, animated visual cues and customized media content as pedagogical tools can simulate student interest in the learning process [29], [30]. For example, one study in the Philippines showed that a developed mobile game intended for basic English language learning can improve student performance particularly in vocabulary, spelling, and grammar [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research showed that health education regarding the use of an assistive device is more effective than lectures because the animation video increases people's engagement and interest [34][35][36]. An educational video may improve the patients' knowledge to a greater extent, so that people understand the content and can correctly answer when they are subsequently tested.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents' knowledge about obtaining antibiotics is associated with their lack of knowledge about antibiotic resistance [33]. Research showed that health education regarding the use of an assistive device is more effective than lectures because the animation video increases people's engagement and interest [34][35][36]. An educational video may improve the patients' knowledge to a great extent, so that people understand the content and can correctly answer when they are subsequently tested.…”
Section: Discussionmentioning
confidence: 99%